The Use of Antibiotics-Impregnated Bone Cement in Reducing Surgical Site Infections in Spine Surgery: A Systematic Review - Purnomo, Alexander E.; Arjuna, Yang Y.E.; Tobing, Jephtah F.L. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2025)
Spine surgeries are one of the most widely performed operations in orthopaedic surgery and neurosurgery. However, one of the most common complications of spine surgeries is surgical site infection (SSI), which is associated with various postoperative morbidities. The use of antibiotics-impregnated bone cement (AIBC) is common in orthopaedic surgeries. Therefore, we aim to provide a comprehensive review of AIBC use in spine surgeries.Data were gathered from PubMed, Europe PMC, and ScienceDirect using keywords associated with AIBC and spine surgeries. We included all publications associated with AIBC and spine surgeries. Studies without full papers, non-English publications, review articles, and animal or cadaveric studies were excluded. The quality of each included studies were assessed using the Newcastle Ottawa Scale and the Joanna Briggs Institute Critical Appraisal for case reports, case series, and quasi-experimental studies.Fifteen studies of 322 patients using AIBC in spine surgery were included. Ten of 15 studies reported 100% infection-free events with AIBC administration with or without given systemic antibiotics. Two studies did not report 100% infection-free events due to methicillin-resistant Staphylococcus aureus (MRSA) infections and technical causes. Three studies reported the use of AIBC without disclosing outcomes. Various types of bacteria ranging from methicillin-sensitive Staphylococcus aureus to MRSA have been discovered, with polymethylmethacrylate and vancomycin being the most frequently used AIBCs.AIBC can be used to prevent postoperative infections due to its high effectiveness, easy administration, and no side effects. Further studies are needed to determine the most appropriate antibiotics, dose, and type of cement.
Keywords: bone cements; antibiotics; impregnated; spine surgeries; surgical site infections